"If we can just 'stall' new unfriendly legislations, the scoreboard is already in our favour": transnational tobacco companies and ingredients disclosure in Thailand. (24th November 2004) - MacKenzie, R; Collin, J; Sriwongcharoen, K; Muggli, M E
Abstract : Objectives: To review the strategies employed by overseas cigarette manufacturers operating in Thailand to obstruct the passage and subsequent enforcement of national public health legislation, specifically the ingredients disclosure provision of the 1992 Tobacco Products Control Act. Methods: Analysis of previously confidential tobacco industry documents relevant to non-compliance with the ingredients disclosure legislation. Results: Requirement for disclosure of ingredients contained in cigarettes contained in the Tobacco Products Control Act was identified by transnational tobacco companies (TTCs) not only as a significant threat to their operations in Thailand, but as a dangerous global precedent. Industry documents reveal a determined campaign to block, stall, or amend the proposed regulation during the legislative process. Industry representatives petitioned the Ministry of Health to revise the requirement from by brand disclosure to a more palatable by company submission. Strategies were adapted in the wake of the passage of the Act. Most significantly, the industry in concert with embassies in Bangkok threatened the Thai government with appeals to international trade bodies on the grounds of violation of international agreements. Industry documents also reveal that as submission of ingredient lists appeared unavoidable, leading companies operating in Thailand endeavoured to confound the disclosure requirement by disguising ingredients and reformulating brand recipes. Conclusions: The evidence presented highlights the importance of ingredients regulation and demonstrates how health policy can be transformed during its implementation. A greater understanding of trade agreements emerges as a priority for global tobacco control.